"Accidental Racist": Stumbling Through the Motions of Racial Reconciliation. Issue 1 (1st January 2016) - Hatch, John B.
Abstract : This article examines country star Brad Paisley's controversial musical dialogue with rapper LL Cool J about race. First, I compare "Accidental Racist" with "Ebony and Ivory" in light of McPhail's notions of rhetorical coherence and complicity. Second, I interrogate Paisley's problematic construction of racial division in light of Gresson's work. Next, I consider how the inclusion of Cool J's voice at least partly challenges Paisley's southern White perspective. In light of Hatch's theory of reconciliation, however, Paisley's pseudo-apology proves self-serving and Cool J's forgiveness is cheap. In the end, their contrived country/hip-hop dialogue dances to the tune of neoliberalism and fails to resonate with either of their core audiences, despite their well-meaning intentions.